Bridging Growth and Sustainability: How Financial Development Shapes the GDP-Climate Finance Nexus - Muhammad Sheeraz; Khadijah Hussain; Muhammad Naeem; Allah Ditta; Nabila Khan; Nouman Ali; Nadeem Iqbal; Faiza Rubab Khan (Kurdish Studies, 2024)
This study investigates the impact of GDP growth on climate finance and the moderating role of financial development in this relationship. It analyses a panel dataset from 2001 to 2021, encompassing the top 25 contributors and affected countries. Employing GMM, static, and dynamic panel techniques, the study presents descriptive statistics, correlation matrices, and regression results. Findings indicate a strong negative association between GDP growth and climate finance, with significant cross-sectional dependence across countries. While GDP per capita shows a linear relationship with climate finance, financial development exhibits a non-linear relationship. The GMM results reveal that GDP growth positively influences climate finance in wealthier economies (Panel A), whereas in lower-income countries, the relationship is negative and quadratic (Panel B), indicating reduced access to climate finance as income rises. Financial development moderates these negative effects by enhancing resource allocation and risk management for climate initiatives. The study emphasizes the need for policies that align economic growth with climate objectives, improve financial systems, promote diverse financial instruments like green bonds, and continuously adapt strategies to ensure effective and sustainable climate finance.
Keywords: 330; Climate finance; financial development; GDP growth; carbon emitter countries; affected countries; quadratic relationship; non-linear relationship